2022
DOI: 10.3389/fonc.2022.778607
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis on the Neutrophil-Lymphocyte Ratio in Rectal Cancer Treated With Preoperative Chemoradiotherapy: Prognostic Value of Pre- and Post-Chemoradiotherapy Neutrophil-Lymphocyte Ratio

Abstract: BackgroundTo evaluate the prognostic value of neutrophil-lymphocyte ratio (NLR) in rectal cancer patients treated with preoperative chemoradiotherapy (CRT) and curative surgery.MethodsA comprehensive search of the EMBASE and PubMed databases was performed to screen studies that compared treatment outcomes according to the pre-CRT and/or post-CRT NLR in patients receiving preoperative CRT and curative surgery for locally advanced rectal cancer. Hazard ratios (HRs) for disease-free survival (DFS) and/or overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Here, we have found an association between worse OS and NLR, an integrated index based on peripheral neutrophils and lymphocytes. The value of NLR in the prognosis of rectal cancer has been extensively described previously 25 , although these results should be read with caution since a large-scale study of 1237 patients could not confirm the prognostic or predictive value of NLR or PLR 26 . Nevertheless, in our study, this score performed better than other scores described in the literature, such as PLR, LMR and SII 27 .…”
Section: Discussionmentioning
confidence: 88%
“…Here, we have found an association between worse OS and NLR, an integrated index based on peripheral neutrophils and lymphocytes. The value of NLR in the prognosis of rectal cancer has been extensively described previously 25 , although these results should be read with caution since a large-scale study of 1237 patients could not confirm the prognostic or predictive value of NLR or PLR 26 . Nevertheless, in our study, this score performed better than other scores described in the literature, such as PLR, LMR and SII 27 .…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, the neutrophil-to-lymphocyte ratio (NLR) has gained attention in recent years as prognostic marker for rectal cancer [126][127][128], which underlines the important role of neutrophils in anti-tumor immunity. Recently, a meta-analysis revealed that elevated NLR before CRT, but not after CRT, is associated with poorer prognosis [126]. Nonetheless, the prognostic impact of intratumoral neutrophils in rectal cancer remains uncertain [129][130][131][132].…”
Section: Neutrophilsmentioning
confidence: 99%
“…High neutrophil blood counts were shown to be associated with worse survival of rectal cancer patients [125]. Furthermore, the neutrophil-to-lymphocyte ratio (NLR) has gained attention in recent years as prognostic marker for rectal cancer [126][127][128], which underlines the important role of neutrophils in anti-tumor immunity. Recently, a meta-analysis revealed that elevated NLR before CRT, M1, which is characterized as immune-activating, anti-tumorigenic and M2 with immunosuppressive, pro-tumorigenic properties.…”
Section: Neutrophilsmentioning
confidence: 99%
“…Various studies have demonstrated that the neutrophil-to-lymphocyte ratio (NLR), a hematologic inflammatory marker, could be a predictive marker for oncological outcomes and response to neoadjuvant chemoradiotherapy (nCRT) in patients with rectal cancer [ 6 9 ]. In a recent meta-analysis of 22 studies comprising 6316 patients, elevated pre-nCRT NLR was found to be strongly associated with worse treatment outcomes in patients with rectal cancer [ 10 ]. Although many studies have explored the correlation between NLR and outcome, few have examined the relationship between NLR and pathologic responses.…”
Section: Introductionmentioning
confidence: 99%